Cost-Effectiveness of Antivenoms for Snakebite Envenoming in 16 Countries in West Africa. - Muhammad Hamza; Maryam A Idris; Musa B Maiyaki; Mohammed Lamorde; Jean-Philippe Chippaux; David A Warrell; Andreas Kuznik; Abdulrazaq G Habib (Public Library of Science (PLoS), 2016)
BACKGROUND:Snakebite poisoning is a significant medical problem in agricultural societies in Sub Saharan Africa. Antivenom (AV) is the standard treatment, and we assessed the cost-effectiveness of making it available in 16 countries in West Africa. METHODS:We determined the cost-effectiveness of AV based on a decision-tree model from a public payer perspective. Specific AVs included in the model were Antivipmyn, FAV Afrique, EchiTab-G and EchiTab-Plus. We derived inputs from the literature which included: type of snakes causing bites (carpet viper (Echis species)/non-carpet viper), AV effectiveness against death, mortality without AV, probability of Early Adverse Reactions (EAR), likelihood of death from EAR, average age at envenomation in years, anticipated remaining life span and likelihood of amputation. Costs incurred by the victims include: costs of confirming and evaluating envenomation, AV acquisition, routine care, AV transportation logistics, hospital admission and related transportation costs, management of AV EAR compared to the alternative of free snakebite care with ineffective or no AV. Incremental Cost Effectiveness Ratios (ICERs) were assessed as the cost per death averted and the cost per Disability-Adjusted-Life-Years (DALY) averted. Probabilistic Sensitivity Analyses (PSA) using Monte Carlo simulations were used to obtain 95% Confidence Intervals of ICERs. RESULTS:The cost/death averted for the 16 countries of interest ranged from $1,997 in Guinea Bissau to $6,205 for Liberia and Sierra Leone. The cost/DALY averted ranged from $83 (95% Confidence Interval: $36-$240) for Benin Republic to $281 ($159-457) for Sierra-Leone. In all cases, the base-case cost/DALY averted estimate fell below the commonly accepted threshold of one time per capita GDP, suggesting that AV is highly cost-effective for the treatment of snakebite in all 16 WA countries. The findings were consistent even with variations of inputs in 1-way sensitivity analyses. In addition, the PSA showed that in the majority of iterations ranging from 97.3% in Liberia to 100% in Cameroun, Guinea Bissau, Mali, Nigeria and Senegal, our model results yielded an ICER that fell below the threshold of one time per capita GDP, thus, indicating a high degree of confidence in our results. CONCLUSIONS:Therapy for SBE with AV in countries of WA is highly cost-effective at commonly accepted thresholds. Broadening access to effective AVs in rural communities in West Africa is a priority.